2010
DOI: 10.1111/j.1466-769x.2010.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Culture theorizing past and present: trends and challenges

Abstract: Over the past several decades, nurses have been increasingly theorizing about the relationships between culture, health, and nursing practice. This culture theorizing has changed over time and has recently been subject to much critical examination. The purpose of this paper is to identify the challenges impeding nurses' ability to build theory about the relationships between culture and health. Through a historical overview, I argue that continued support for the essentialist view of culture can maintain a lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 50 publications
0
27
0
2
Order By: Relevance
“…Although researchers in the social sciences have been exploring and developing the concept of cultural fluidity for the last two decades (Gilroy, 1993;Bhaba, 1994;Hall, 2000;Bauman, 2005), there remains a tendency for medicine to pathologise cultures and to associate cultural 'traits' with disease processes (Ahmad and Bradby, 2007). Recent research by Vanderberg (2010), examining the relationships between culture, health and nursing practice, found that nurses continue to support a view of culture that is fixed and demonstrate a limited engagement in the complexity of culture. Professional-client interaction and knowing the client have a long and important tradition in primary health care and the results of this study suggest that in trying to know the client, and to cope with the uncertainty of culture, the health visitors tried to squeeze cultures into defined categories and risked stereotyping and prejudice.…”
Section: Discussionmentioning
confidence: 99%
“…Although researchers in the social sciences have been exploring and developing the concept of cultural fluidity for the last two decades (Gilroy, 1993;Bhaba, 1994;Hall, 2000;Bauman, 2005), there remains a tendency for medicine to pathologise cultures and to associate cultural 'traits' with disease processes (Ahmad and Bradby, 2007). Recent research by Vanderberg (2010), examining the relationships between culture, health and nursing practice, found that nurses continue to support a view of culture that is fixed and demonstrate a limited engagement in the complexity of culture. Professional-client interaction and knowing the client have a long and important tradition in primary health care and the results of this study suggest that in trying to know the client, and to cope with the uncertainty of culture, the health visitors tried to squeeze cultures into defined categories and risked stereotyping and prejudice.…”
Section: Discussionmentioning
confidence: 99%
“…47 Healthcare providers who understand the social, historical, political, institutional, and economic context healthcare recipients experience will be better able to understand and intervene in structural mechanisms that exclude and unprivilege the perspective of those recipients. 48 The use of a caring multiculturalism that is attentive to the power dynamics that privilege certain moral decisions over others could be feasible in resolving this ethical dilemma. 47 The practice of cultural safety further illuminates the dynamics of power differentials in clinical settings by applying reflective practice and agency 49 and may ultimately point the way to resolving power differentials and ethical conflicts.…”
Section: Cultural Safety and Relational Aspects Of Communication Betwmentioning
confidence: 99%
“…This kind of theorizing is thus more problematic than valuable. By assuming that people of a certain group share static traits, values, and beliefs, cultural categories become legitimized as objective truths, as opposed to social constructions (Vandenberg, ). It is important to acknowledge that in this increasingly globalized world, culture is fluid, rather than static, and that specific cultures cannot be captured, standardized, and taught to students.…”
Section: Introductionmentioning
confidence: 99%